Fulminant amebic colitis: A study of six cases - Nisheena R; Ananthamurthy Anuradha; Inchara Y (Wolters Kluwer Medknow Publications, 2009)
Background: Amebic colitis although common, rarely presents as fulminant colitis which has a high morbidity and mortality unless treated promptly and appropriately. Aim: To study the clinical, morphological features and outcome of fulminant amebic colitis (FAC). Materials and m0 ethods: A retrospective study of six patients who underwent surgical resections from 2002-06 and were diagnosed with FAC, was carried out. The morphological features assessed included the average number of trophozoites per high-power field and the depth of invasion of trophozoites into the muscularis propria. Results: The study included five adults and one child who underwent surgery for fulminant colitis. Interestingly, a definite preoperative diagnosis of amebic colitis was made only in one patient and suspected in another. Intraoperatively, multiple perforations of the intestine with peritonitis were the most common findings. Gross examination typically revealed multiple ulcers with exudate and intervening normal mucosa. Microscopically, ulceration and myonecrosis with trophozoites within the exudate were seen in all cases. Trophozoites invading the muscularis propria were seen in five cases. Of the cases that showed myoinvasion by trophozoites, two patients expired within two weeks of surgery. One of the patients who expired also showed co-infection with Actinomyces. Conclusion: FAC is an uncommon outcome in amebic colitis with a high mortality requiring prompt surgical intervention.